Kształcenie nawyków o zdrowym stylu życia oraz sposobie odżywiania się dziewcząt w okresie adolescencji = Learning habits about a healthy lifestyle and the way girls eat during adolescence - Mydłowska, Beata; Mydłowska, Monika (Vilnius: Mykolas Romeris Universitetas)
The subject of the article is the lifestyle and ways of feeding girls during adolescence. The main goal of the article was to determine the knowledge about healthy lifestyle and diets among girls during adolescence. During the test procedure, an attempt was made to answer the following specific questions:
Keywords: zdrowy styl życia; wiedza o zdrowym stylu życia; sposób odżywiania się; dziewczęta; zaburzenia odżywania; adolescencja; adolescence; healthy lifestyle; knowledge of a healthy lifestyle; diet; girls; eating disorders